2012
DOI: 10.1016/j.bbrc.2012.05.028
|View full text |Cite
|
Sign up to set email alerts
|

TRIM59 interacts with ECSIT and negatively regulates NF-κB and IRF-3/7-mediated signal pathways

Abstract: Innate immune responses are triggered by pathogen-associated molecular patterns (PAMPs) through pattern recognition receptors (PRRs) and then activate intracellular signaling pathways including NF-B and interferon regulatory factors. Recently, it has been reported that tripartite motif (TRIM) proteins function as crucial regulators via ubiquitin-mediated modifications for these signaling pathways. In this study, we showed that one of the TRIM family ubiquitin ligases, TRIM59, interacts with ECSIT as an adaptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 28 publications
3
51
0
Order By: Relevance
“…Hence, different TRIM proteins are predicted to regulate diverse host defensive strategies against a single pathogenic agent. Further, TRIM59 was shown to interact with ECSIT, an adaptor protein in the TLR pathway (44). In agreement with our results (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, different TRIM proteins are predicted to regulate diverse host defensive strategies against a single pathogenic agent. Further, TRIM59 was shown to interact with ECSIT, an adaptor protein in the TLR pathway (44). In agreement with our results (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…2a), TRIM59 was found to inhibit type I IFN production in vitro, possibly by inhibition of phosphorylation or dimerization of IRF3 and IRF7. While TRIM59 was shown to inhibit NF-B in vitro (44), we and others demonstrated that TRIM13 can enhance NF-B promoter activity (Fig. 2f) (11,12).…”
Section: Discussionmentioning
confidence: 59%
“…For example, we revealed that TRIM40, which is one of the TRIM family of ubiquitin ligases, enhances neddylation of IKKγ and inhibits the activity of NFκB-mediated transcription [25]. Moreover, we found that TRIM59 interacts with a signal adaptor protein, evolutionarily conserved signaling intermediate in Toll pathways (ECSIT), and negatively regulates NFκB and IRF3/7 signal pathways [24]. It has also been reported that Cactin inhibits NFκB and…”
Section: Trim39 Negatively Regulates Nfκb Signalingmentioning
confidence: 79%
“…Based on our previous findings that some of the TRIM family proteins affect the stabilities of their binding proteins [13,14,[24][25][26], we speculated that TRIM39 affects the stability of Cactin. Although we assumed that TRIM39 promotes degradation of Cactin, protein stability analysis with cycloheximide revealed that overexpression of TRIM39 WT or that of ΔRING promoted the stabilization of Cactin protein (Fig.…”
Section: Trim39 Stabilizes Cactinmentioning
confidence: 99%
“…Recently, ECSIT has been found to induce mitochondrial reactive oxygen species (mROS) generation downstream of TLR1, TLR2 and TLR4, which is critical for mouse macrophage bactericidal activity [21]. Although it has been reported that TRIM59 inhibits VISA-induced activation of IRF3 and NF-κB by interacting with ECSIT [22], it is unclear how ECSIT is involved in virus-triggered type I IFN signaling. In this report, we found that ECSIT acted as an essential scaffolding protein that bridged RIG-I and MDA5 to VISA, and thereby plays an essential role in RLR-mediated type I IFN induction and cellular antiviral responses.…”
Section: Introductionmentioning
confidence: 99%